Growth/no-growth models of in-vitro growth of Penicillium paneum as a function of thyme essential oil, pH, aw, temperature. (October 2019) - Debonne, Els; Vermeulen, An; Van Bockstaele, Filip; Soljic, Irena; Eeckhout, Mia; Devlieghere, Frank
Abstract: The aims of this study were (i) screening of antifungal activity of thyme essential oil on Penicillium paneum ; (ii) development of growth/no-growth models (G/NG); and (iii) validation of the G/NG models by performing bread baking trials. The screening method was based on the measurement of fungal growth in a semi-solid medium through optical density. The combined influence of a w (0.88–0.97), pH (4.8–7.0), temperature (22 and 30 °C), time (0–144 h) and varying concentrations of thyme oil (0–2 μL/mL YES) were assessed. Growth of P. paneum at a w 0.88 was significantly reduced compared to a w 0.93–0.97. A slight pH effect was observed at a w 0.93; growth was delayed at pH 6 compared to pH 4.8. The lowest concentration of thyme oil preventing growth during 144 h of incubation was 1 μL/mL medium. According to the results of the shelf-life test of par-baked bread, fungal growth was inhibited for more than 45 days using 0.3 mL thyme oil/100 g dough. To conclude, this study recognized the potential of using G/NG models to develop better product formulations and to facilitate product innovation. Highlights: The effects of aw, pH, temperature and thyme oil were assessed on the growth of Penicillium paneum. Growth/no-growth models were develop to describe these effects on a semi-solid medium. Efficiency of thyme oil in bread was less than in the semi-solid medium. On par-baked bread fungal growth was inhibited for more than 45 days using 0.3 mL thyme oil/g dough.